Study of Heritability and Genetic Advance of Some Physiological Characters and Yield as Influenced by Sowing Date of Barley Genotypes - Alam, MZ; Haider, SA; Paul, NK (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Barley; sowing date; nitrogen utilizationBangladesh j. genet. biotechnol. 5 (1&2): 33-35, 2004 (June & December)